Whole-body pre-cooling and heat storage during self-paced cycling performance in warm humid conditions - Kay, D.; Taaffe, D. R.; Marino, F. E. (Journal of Sports Sciences, 1999)
The aim of this study was to establish the effect that pre-cooling the skin without a concomitant reduction in core temperature has on subsequent self-paced cycling performance under warm humid (31oC and 60% relative humidity) conditions. Seven moderately trained males performed a 30 min self-paced cycling trial on two separate occasions. The conditions were counterbalanced as control or whole-body pre-cooling by water immersion so that resting skin temperature was reduced by 5-6oC. After pre-cooling, mean skin temperature was lower throughout exercise and rectal temperature was lower (P < 0.05) between 15 and 25 min of exercise. Consequently,heat storage increased (P < 0.003) from 84.0 +/- 8.8 W.m-2 to 153 +/- 13.1 W.m-2 (mean sx) after pre-cooling, while total body sweat fell from 1.7 +/- 0.1 l.h-1 to 1.2 +/- 0.1 l.-1 (P < 0.05). The distance cycled increased from 14.9 +/-0.8 to 15.8 +/- 0.7km (P < 0.05) after pre-cooling.The results indicate that skin pre-cooling in the absence of a reduced rectal temperature is effective in reducing thermal strain and increasing the distance cycled in 30 min under warm humid conditions.